PENGARUH MEDIA PEMBELAJARAN WORDWALL TERHADAP HASIL BELAJAR IPAS KELAS IV SDN 104255 PALUH SIBAJI - Rahmayanti, Rahmayanti; Beta Rapita Silalahi; Safrida Napitupulu; Putri Juwita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to test the effect of using Wordwall learning media on the learning outcomes of class IV SDN 104255 Paluh Sibaji. The learning process of Science, indicates that student learning outcomes are not optimal. Wordwall learning media was chosen as an intervention because of its potential in increasing motivation and learning interactivity. This study uses a quasi-experimental quantitative research method using the Nonequivalent Control Group Design. The data collected include, quantitative data obtained from pretest scores in the form of questions on photosynthesis material. Then qualitative data in the form of student response questionnaire data to the WordWall learning media. Data collection techniques in this study are Pretest and posttest. The pretest was carried out at the beginning of the learning activity while the posttest was carried out at the end of learning, and student questionnaire data which is additional data aimed at finding out students' opinions about the WordWall learning media in Science learning. The results of the analysis showed that the average posttest score of students in the experimental class was 82.75, while the control class obtained an average of 72.10. Based on the t-test, the sig value was obtained. (2-tailed) of 0.001 < 0.05 which indicates a significant increase between the two classes. Then, the results indicate that the Wordwall learning media has a positive and significant influence on improving the learning outcomes of class IV students of SDN 104255 Paluh Sibaji. Thus, the use of WordWall media has proven effective in improving student learning outcomes and can be an innovative alternative in the learning process.